The Influence of Financing, Service-Based Income, and Internal Factors on Net Operating Margin in Islamic Commercial Banks - Raden Marsha Ananda Putri; Tenny Badina; Ahmad Fatoni (Department of Islamic Banking, 2024)
This study examines the impact of the Financing to Deposit Ratio (FDR), Fee-Based Income (FBI), Operating Expenses to Operating Income (BOPO), and Non-Performing Financing (NPF) on the Net Operating Margin (NOM) of Islamic Commercial Banks (BUS) in Indonesia from 2017-2023. Amid concerns about the sustainability of Islamic banks due to excessive reliance on FBI rather than financing (FDR). Panel data from secondary data Islamic Commercial Banks (BUS) financial statements and the Financial Services Authority (OJK) with Eviews 12. The results show that an increase in FDR positively affects profitability (NOM), while excessive reliance on FBI significantly negatively impacts profitability (NOM). BOPO also has a significant negative impact on profitability (NOM), whereas Non-Performing Financing (NPF) does not significantly affect profitability (NOM). These findings suggest that Islamic Commercial Banks should optimize FDR and BOPO, carefully manage dependence on FBI, and diversify income and risk strategies to enhance profitability.